HUBUNGAN INDEKS MASSA TUBUH DENGAN FLEKSIBILITAS OTOT HAMSTRING PADA PEMAIN SEPAK BOLA AMATIR USIA 10 - 13 TAHUN - Muhamad Rafly Ar Rasyid, (2023)
Background: Flexibility is the ability to perform movements in the space of joint motion that is affected by gender, age, and elasticity of tendons, muscles, and ligaments. Good flexibility in the hamstring is evidenced by the ability of the hamstring muscles to contract concentrically and eccentrically. Flexibility is often described as an indicator of a football player's playing time and some factors support a player's performance, such as ideal height and weight. The ability of soccer players to gain flexibility depends on their body mass index (BMI). Purpose: To analyze the relationship between body mass index relationship to hamstring muscle flexibility in amateur football players aged 10-13 years. Design: The method used in the study is the whole rational type. The number of samples required in this study is 83 students in SSB Metro Kukusan, Depok. The parameters used in measuring height are microtoice and hamstring flexibility using sit and reach test. Results: This study used SPSS 25 and obtained results of p = 0.646 with a correlation coefficient of -0.055 which means there is no relationship between BMI and flexibility. In conclusion: there is no relationship between BMI and hamstring muscle flexibility in amateur soccer players aged 10-13 years.